2010
DOI: 10.1093/aje/kwq113
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Circulating 25-Hydroxyvitamin D: Cohort Consortium Vitamin D Pooling Project of Rarer Cancers

Abstract: Low vitamin D status is common globally and is associated with multiple disease outcomes. Understanding the correlates of vitamin D status will help guide clinical practice, research, and interpretation of studies. Correlates of circulating 25-hydroxyvitamin D (25(OH)D) concentrations measured in a single laboratory were examined in 4,723 cancer-free men and women from 10 cohorts participating in the Cohort Consortium Vitamin D Pooling Project of Rarer Cancers, which covers a worldwide geographic area. Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
119
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(149 citation statements)
references
References 56 publications
24
119
6
Order By: Relevance
“…A significant negative correlation was found between 25(OH)D and age in our patients, in agreement with the literature [20]- [22]. Significant associations were also observed with menopause extension, BMD and BMI, according to other authors' reports [23]- [26]. However, after age adjustment, in our sample no association was found among vitamin D levels and hip BMD, and only the association between 25(OH)D and BMI remained significant.…”
Section: Discussionsupporting
confidence: 92%
“…A significant negative correlation was found between 25(OH)D and age in our patients, in agreement with the literature [20]- [22]. Significant associations were also observed with menopause extension, BMD and BMI, according to other authors' reports [23]- [26]. However, after age adjustment, in our sample no association was found among vitamin D levels and hip BMD, and only the association between 25(OH)D and BMI remained significant.…”
Section: Discussionsupporting
confidence: 92%
“…5 Sex-specific quartiles were used in nutrition analyses. 6 Cutoffs for quartiles-men: 0.6, 1.0, and 1.7; women: 0.5, 1.0, and 1.5. concentrations in our study, whereas the evidence from other studies is mixed (15,(55)(56)(57)(58)(59). Surprisingly, we found that sunscreen use was associated with slightly higher serum 25(OH)D concentrations; this may be because individuals who regularly use sunscreen have greater sun exposure, but may use sunscreen ineffectively (7,60).…”
Section: Discussioncontrasting
confidence: 80%
“…139 Excessive alcohol consumption is linked to lower 25-(OH)D concentrations, 140 but moderate intake is consistently reported to relate to better VitD status. 30,67,131,141,142 Strengths of our study include the large number of subjects for whom 25-(OH)D measurements were available and the wide age distribution, which lead us to consider our cohort as being representative of the general population of a Mediterranean island. The inherent limitations of our work lie in its retrospective design and the mixed population studied (in-and outpatients), although no significant differences between the two groups were found.…”
Section: 55mentioning
confidence: 99%